Activated Carbon From Palm Fibres Used as an Adsorbent for Methylene Blue Removal - Maia, Lana S.; da Silva, Andressa I. C.; Carneiro, Emanuel S.; Monticelli, Francisco Maciel [UNESP]; Pinhati, Fernanda R.; Mulinari, Daniella R. (Springer Nature, 2021)
Abstract: In this paper, activated carbon was synthesized by chemical activation using sodium hydroxide as an activating agent from residues of the stem and sheath palm fibres, and their efficacies in the removal of methylene blue were evaluated. The materials were characterized by techniques like thermogravimetric analysis (TGA), Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), scanning electron microscopy (SEM), and surface area (BET). The influence of two experimental factors, such as contact time (10 to 70 min) and initial dye concentration (25, 50, 100, 250, and 500 mg.L− 1) was investigated. The adsorption process was followed by the Langmuir isotherm model with a maximum adsorption capacity of 110.79 and 162.54 mg.g− 1for stem and sheath palm. Results demonstrated that activated carbon from palm fibres have characteristics necessary for the removal of methylene blue. The equilibrium data were well adjusted in the Langmuir isotherm model, which confirms that the adsorption was heterogeneous and occurred through physicochemical interactions. Graphic Abstract: [Figure not available: see fulltext.]
Keywords: Activated carbon; Adsorption; Methylene blue; Palm fibres residue